The amphibians and reptiles of Malinau Region, Bulungan Research Forest, East Kalimantan: annonated checklist with notes on the ecological presence of the species and local utilization - Iskandar, D.T. (Center for International Forestry Research, 2004)
The amphibians and reptiles of CIFOR's field site in Malinau were investigated and observed followed by interviews with local people. A total of 97 species were noted, and 76 among them were confirmed. Malinau is an ecologically rich area for an exploited forest and researchers found less logging damage than previously believed. This study indicates that current logging activity has only minimal impact on frog diversity. Although their abundance is relatively low, the present study is unable to link this fact with logging activities because diversity levels are similar to those in undisturbed forests. All streams contain roughly the same species, indicating that the habitat itself is essentially homogenous. Knowledge of the habitat of amphibian species should be explored more deeply for future monitoring of logging activities. The local people used turtles, monitor lizards and phythons as food, but rarely eat frogs. Therefore the reasonfor the low number of large adults frogs of the genus Limmonextes is most probably the result of natural causes and not by human exploitation.